A Survey on Recent Advances to Read Handwritten Devanagari Script - Kolte, Gauri; Fernandes, Jennifer; Vishwakarma, Prashant; Nikharge, Samira; Deore, Shalaka (International Journal of Computer Sciences and Engineering, 2019)
In the realm of advances in Processing Capabilities as well as Algorithms and their Efficiencies, transliteration mechanisms between Handwritten and Digital data namely called as Recognition Systems or Machine Reading Systems have been able to reach reliable precision. Devanagari and its variant scripts are widely used in the Indian Subcontinent. Being used by the second largest population in the world, it is practical to have research for Devanagari as well. While the current advances in recognition of Devanagari suggest requirement of more work and scope for accuracy levels, this survey aims to enlist the approaches taken in research to read handwritten Devanagari script. Citing works from different papers using different classifiers and techniques, it attempts to compare results and also imply the need of taking research forward. The survey contains methodologies followed in recent times, mentions data collection strategies or datasets available, uses classifiers and their recognition rates respectively.